Anonymous Bodies? The Process of Disciplining in Tuberculosis Sanatoriums (Theatrum historiae, 2021)
This paper presents a normative analysis of the internal regulations (house rules) of tuberculosis sanatoriums during the first half and the early second half of the 20th century. It analyses regulations for children and adult patients, enabling a direct comparison of the rules applicable to each group and a characterisation of the specific rules applied to children. The second part of the study investigates patients’ reactions to the strict and monotonous regime in sanatoriums, which was controlled and enforced by the staffof these institutions. The analysis of social practices draws on a unique set of documents detailing complaints about patients’ behaviour written by Dr. Svatopluk Basař, the director of the Na Pleši sanatorium.
Keywords: sanatoriums; tuberculosis; internal regulations (house rules); discipline; normativity; Na Pleši sanatorium